A percepção do pai frente ao nascimento do seu filho - Silveira, Isolda Pereira da (2004)
The aim of this study of qualitative nature was to learn about a father’s perception in the face of his child’s birth. It was carried out in the puerperium unit of a big public maternity hospital associated to the national health system in the city of Fortaleza-CE. The subjects of this research were fifteen fathers who were visiting their children and wives. Data was collected through semi-structured interviews. The outcome suggests three categories: a father waiting for his child; emotions experienced by the father; desire to participate in the procedures of birth. We concluded that a father’s participation should be encouraged since it is important for the well being and safety of the family during the procedures of birth. Therefore, it is necessary to establish in health institutions new postures concerning the presence of a father during the birth.